PEMAKAIAN ISTILAH BAHASA SANSKERTA PADA NAMA DIRI DI DALAM PRASASTI POH (827 ÇAKA): TINJAUAN PERSPEKTIF IDENTITAS - Kayato Hardani (Berkala Arkeologi, 2018)
Proper names in general use as the individual differentiator within the community as well as the identity. Parent in giving name on their newly born baby is often based on some motivation. Proper names can be analyzed linguistically because it contains elements of the sign that serves referential as well as vocative. The proper names is a part of the human being itself, so that in every interaction within society, someone always conscious of his own identity for his own interests, the other person and society as his place of life and interaction. Diachronically the development of language, including the use of the name itself can be traced back its presence through written inscriptions in the form of inscriptions. The writing of the proper name in Poh inscription is explicitly only as a list of attendees (witnesses) who attended the inauguration ceremony. Starting from this point can be found the use of the name of the old Javanese period. This study aims to understand the construction and meaning in the proper name found in the Poh Inscription using an identity perspective. The method used in this study is descriptive qualitative which begins with observing and analyzing proper names using Sanskrit language elements.